THE TRANSFORMATION OF LEARNING IN THE DIGITAL ERA: TEACHERS’ PERSPECTIVES ON DIGITAL MEDIA USE AND ITS IMPLICATIONS FOR SCIENCE EDUCATION - Nurdini Nurdini; Solehkun Kodir; Nuzulira Janeusse Fratiwi; Hera Novia; Nur Habib Muhammad Iqbal (Physics and Science Education Journal (PSEJ), 2025)
This study aims to explore junior secondary school teachers’ perspectives on the use of digital media and its implications for the transformation of science education in the digital era. This study employed a survey research design. Data were collected from 1,622 teachers across 38 provinces in Indonesia using a structured questionnaire encompassing five key domains: the intensity and types of digital media use, challenges in implementation, expected forms of support, and the impact on the learning process. The instrument underwent expert validation by three specialists in educational technology and science education. The content validity results indicated an S-CVI score of 0.95 for content relevance, 0.93 for clarity of wording, and 0.93 for alignment with the research objectives. Data were analyzed using descriptive statistics to summarize the trends in teacher responses. The results show that 87.8% of teachers were accustomed to using digital technology in learning, with the highest frequency of use falling under several times per week (64.8%). The main barriers identified were limited device access (67.7%), unstable internet connectivity (60.7%), and insufficient training (56.6%). Most teachers emphasized the need for sustainable and subject-relevant digital competency training. The findings highlight that the transformation of science education in the digital era depends not only on infrastructure availability but also on the pedagogical capacity of teachers to utilize digital media in contextual, exploratory, and, scientific ways.